Vol 2 no 1 EKONOMI KERAKYATAN DALAM PERSPEKTIF EKONOMI SYARI'AH: PERAN BUMDES DALAM MENINGKATKAN EKONOMI MASYARAKAT DALAM PRESPEKTIF EKONOMI SYARI’AH (STUDI KASUS BUMDES LENTERA NEGERI DESA BRANGSONG KECAMATAN BRANGSONG KABUPATEN KENDAL) - hani, umi (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2024)
This research is motivated by the existence of economic activities that are growing every year, thus making researchers interested in these economic activities. Economic activities are very important and beneficial for the community because they can increase income and improve the community's economy so that they can meet the needs of life. To implement economic activities, the community needs to work and try, with this work can change people's lives for the better and is expected to be able to shape individuals and the public into humans who are useful for the community and the state. This research is a qualitative field research with data collection methods using observation, interview, and documentation methods. As for the validity test of the data, the author uses the extension of participation, diligence of observation and detailed description, for data analysis the author uses qualitative descriptive analysis, which is in the form of data using Lexy J. Moeloeng's theory, namely data reduction, data presentation and conclusion drawing with verification.The result of the analysis in writing this thesis is the implementation mechanism including economic activities, implementation, and supporting and inhibiting factors.